A PROPOSITION OF KNOWLEDGE MANAGEMENT METHODOLOGY FOR THE PURPOSE OF REASONING WITH THE USE OF AN UPPER-ONTOLOGY - Szymański, Kamil; Dobrowolski, Grzegorz; Koźlak, Jarosław; Zygmunt, Anna (Computer Science, 2013)
This article describes a proposition of knowledge organization for the purpose of reasoningusing an upper-ontology. It presents a model of integrated ontologies architecture whichconsists of a domain ontologies layer with instances, a shared upper-ontology layer withadditional rules and a layer of ontologies mapping concrete domain ontologies with the upperontology.Thanks to the upper-ontology, new facts were concluded from domain ontologiesduring the reasoning process. A practical realization proposition is given as well. It is basedon some popular SemanticWeb technologies and tools, such as OWL, SWRL, nRQL, Prot´eg´eand Racer.